Pengolahan Data Statistik Rumah Sakit Bhayangkara Padang Menggunakan Microsoft Excel Periode 1 Januari – 31 Maret - Ridho Penelly; Sayati Mandia; Yastori Yastori (AKADEMI PEREKAM DAN INFORMASI KESEHATAN (APIKES) IRIS PADANG, 2022)
Medical record is a file that contains notes and documents about the patient's identity, examination, actions, and other services that have been provided to patients. The purpose of this paper is to determine the processing of statistical data at Bhayangkara Padang Hospital using Microsoft Excel for the period January 1 – March 31, 2015 with 385 inpatients and 62 beds. Then, the data was processed using a computer using the Microsoft Excel application program. Statistical processing was analyzed and presented in the form of tables and graphs by Barber Johnson. Based on the RL4a report, the most age group is the age group of 25-44 years with 247 patients with male sex as many as 12 patients, and female as many as 235 patients, while based on the disposition of life 385 patients, and 0 patients who died. After processing the data, the BOR was 18.3%, rounded to 18%, the BOR value obtained was inefficient. BTR as much as 6.21 times, because the calculation of the BTR figure is per year, then BTR cannot be calculated. IT is 11.8 days or 12 days, the IT value obtained is inefficient. And ALOS is 2.68 days or 3 days, the ALOS value obtained is inefficient.